Coupled phenomena in environmental geotechnics : from theoretical and experimental research to practical applications : proceedings of the International Symposium, ISSMGE TC 215, Torino, Italy, 1-3 July 2013 /: from theoretical and experimental research to practical applications : proceedings of the International Symposium, ISSMGE TC 215, Torino, Italy, 1-3 July 2013. (©2013) - Unknown
No abstract available